THE FIG LEAF TEA: INNOVATION OF THE PLANT OF HEAVEN RICH IN BENEFITS AS AN OPTIMIZATION OF HALAL INDUSTRY - Wasito Wasito; Siti Maria Wardayati; Alfi Arif; Septarina Prita Dania Sofianti; Iswi Hariyani; Mohammad Fiqkri; Raissa Aulia Salsabila; Nadya Astadewi Putri A (UPT Penerbitan Universitas Jember, 2022)
The purpose of the service is to produce a teen tea business idea which is a healthy drink made from leaves that is rich in benefits, especially in increasing the body's immunity. Teen tea processing can be a means to increase the existence of fig leaves which are considered useless and cannot be processed. Teh Teen can be a solution to problems related to the low public interest in vegetables, especially people with unhealthy lifestyles and have a busy or busy daily life through the practical packaging of tea bags. The public can buy teen tea online or offline at an affordable price, which is IDR 10,000 for 5 pcs. Reviewing the human resource, marketing, operational and financial aspects of Teh Teen products is very feasible or feasible. The proof is in the aspect of the fund budget plan which always increases profits from year to year as well as the investment valuation analysis using the Payback Period Method that states that it is possible to run. Teh Teen's innovative products can support Indonesia's potential to become a halal industry and contribute to improving the Indonesian economy. The output of the dedication was in the form of a teen tea business plan product and won 2nd place in the Jember Islamic Economic Fair Contest at the University of Jember at the National level. Keywords: Fig Leaf Tea, Business plan product, halal industry